Antimicrobial activity of chlorophyll-based solution on Candida albicans and Enterococcus faecalis - Lilian Eiko MAEKAWA; Roberta LAMPING; Sidnei MARCACCI; Marcos Yasunori MAEKAWA; Maria Renata Giazzi NASSRI; Cristiane Yumi KOGA-ITO (Revista Sul-Brasileira de Odontologia, 2008)
Chlorophyll is a phytotherapic substance that presents curing properties, however it is rarely used in Dentistry. Objective: Objective to analyze the antimicrobial activity of a chlorophyll-based solution on isolates of Candida albicans and Enterococcus faecalis by agar dilution method. Material and Methods: oral isolates and Material and Methods Candida albicans reference strain (ATCC 18804) and Enterococcus faecalis (ATCC 29212) were included in the study. Chlorophyll extract was diluted in Sabouraud dextrose or brain heart infusion (BHI) agar, according to the testing microorganism and poured in Petri plates, obtaining the final concentrations of 50%, 25%, 12.5%, 6%, 3% and 1.5%. C. albicans and E. faecalis strains were plated with the aid of a Steers’ inoculator. Plates were incubated at 37°C for 48 h for C. albicans and at 5% CO2 for E. faecalis. The experiments were performed in duplicate. Results: the results showed that the concentrations 50% and 25% chlorophyll extract were effective against C. albicans. E. faecalis grew in the presence of all the concentrations. Conclusion: Conclusion: Conclusion: chlorophyll-based solution presents effective antimicrobial activity of C. albicans but did not present any activity on E. faecalis.